Inequality of income, asset and debt of inland fishers in the Theni District of Tamil Nadu, India - Radhakrishnan, Kalidoss; Marimuthu, R.; Rajakumar, M.; Qureshi, Neha W. (Indian Journal of Fisheries, 2017)
In the present study, an attempt was made to measure the impact of inequality on income, asset and debt of inland fishers in the Theni District of Tamil Nadu, India. A total of 140 respondents were surveyed for this work. Gini index (GI) was applied to measure the income inequality and multiple regression was done to identify the influencing variable of asset and debt. Higher income was observed in non-fishing activities than those of the fishing and fishing related works while higher income equality was recorded in fishing. Among assets, fishing gear, craft, television and land had lesser inequality (GI 0.06 to 0.41) while furniture and livestock had higher inequality (GI 0.0 to 0.80). Average debt was found to be higher among institutional sources than that of the non-institutional ones, whereas, a minimum GI (0.59) was recorded in Vagai and the maximum GI (0.76) in Kullapuram. Results of the study indicate that there is a need for curtailing the credit from non-institutional sources, which burden fishers and affects their economic status. Also, the fishing sector in Tamil Nadu needs proper policy attention regarding education and well-designed market policies and institutions to minimise the inequality that is plaguing the sector.